INVESTIGATING THE IMPACT OF IMPLEMENTATION OF KURIKULUM MERDEKA ON TEACHER INSTRUCTIONAL STRATEGIES IN SMAS KARYA BUDI PUTUSSIBAU - Putri, Aprilian Novita Putri; Sahrawi; Hafiz, Maliqul (Journal of Language Teaching Lingustics and Literature, 2025)
This study explores the impact of the implementation of the Kurikulum Merdeka on English teachers’ instructional strategies at SMAS Karya Budi Putussibau. Employing a qualitative case study approach, data were collected through interviews, classroom observations, and document analysis involving two English teachers who had implemented the curriculum for more than one year. Thematic analysis revealed five major instructional strategies: differentiated instruction, student-centered learning, project-based learning, collaborative learning, and technology integration. These strategies reflect the shift toward more flexible, contextual, and learner-centered approaches promoted by the Kurikulum Merdeka. The curriculum also positively influenced students' motivation and participation while encouraging teachers to be more creative and adaptive in their lesson planning. However, the study also identified challenges, including limited facilities and the need for continuous teacher training. This research contributes to the growing body of literature on curriculum reform in Indonesia and offers insights for educators and policymakers in optimizing curriculum implementation. Keywords: Curriculum Implementation, Curriculum Impact, Instructional Strategies, Kurikulum Merdeka